Stabilization of glaucoma after non-perforating deep sclerectomy with laser trabeculoplasty ab externo (Ukrainian Journal of Ophthalmology, 2025)
Background: Non-perforating deep sclerectomy (NPDS) is an efficacious and safe procedure for the treatment of glaucoma.Purpose: To examine the effect of NPDS alone vs NPDS with a simultaneous laser trabeculoplasty (LT) ab externo in patients with primary open-angle glaucoma (POAG).Material and Methods: Patients of group 1 (94 patients; 94 eyes) underwent a combined procedure of NPDS and LT ab externo, whereas those of group 2 (control group; 80 patients; 80 eyes) underwent NPDS alone for POAG.Results: In group 1, mean intraocular pressure (IOP) before surgery and at month 12 and month 24 was 27.1 ± 2.2 mm Hg, 19.1 ± 1.2 mm Hg and 19.8 ± 2.6 mm Hg, respectively, vs 26.9 ± 2.0 mm Hg, 20.6 ± 1.5 mm Hg, and 21.5 ± 1.2 mm Hg, respectively, in group 2. In addition, in the combination procedure group, mean Mean Deviation (MD) before surgery and at month 12 and month 24 was -8.1 ± 6.9 dB, -8.5 ± 6.9 dB, and -8.9 ± 7.0 dB, respectively, vs -8.8 ±7.6 dB, -9.2 ± 7.6 dB, and -9.7 ± 7.4 dB, respectively, in the control group. Moreover, in group 1, mean retinal nerve fiber layer (RNFL) thickness before surgery and at month 12 and month 24 was 65.3 ± 16.5 nm, 64.2 ± 16.3 nm and 63.6 ± 15.9 nm, respectively, in the combination procedure group, vs 67.1 ± 14.9 nm, 65.8 ± 15.2 nm and 62.3 ± 15.4 nm, respectively, in group 2.Conclusion: NPDS with a simultaneous LT ab externo slows the progression of glaucomatous optic neuropathy.
Keywords: primary open-angle glaucoma; intraocular pressure; optic disc; non-perforating deep sclerectomy; laser trabeculoplasty; static automated perimetry; optical coherence tomography